How does cultural and colonial heritage affect optimal branding strategies? Evidence from the rice sector in Senegal - Britwum, Kofi; Demont, Matty (Wiley, 2024)
Africa's cultural and colonial heritage has profoundly segmented rice markets. Whereas in ancient centers of rice domestication, consumers maintained preferences for local rice consistent with their cultural heritage, preferences have shifted toward imported Asian rice in coastal areas around seaports, due to prior exposure to colonial import substitution policies. To enhance the competitiveness of locally produced rice relative to imported versions, it is necessary to tailor new local rice products to both market segments. A study was conducted in Senegal to test branding strategies for local rice in a country where both market segments coexist. Brands that mimic local and international labels were developed for local rice, and urban consumers bid to upgrade non‐preferred to preferred brands through the Becker–DeGroot–Marschak (BDM) mechanism. Contrary to expectations, results from an endogenous switching regression show that descendants from ancient Senegalese rice domesticators placed premiums on local rice with foreign‐looking brands, indicating that foreignness is perceived as a quality cue even in market segments rooted in cultural heritage. Thus, branding local rice using a combination of local and foreign cues could be an effective strategy in promoting domestic rice to both segments shaped by cultural and colonial heritage.